2005
DOI: 10.1111/j.1365-2664.2005.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial association of Mycobacterium bovis infection in cattle and badgers Meles meles

Abstract: Summary 1.Control of zoonotic disease is difficult to achieve when populations of multiple hosts, particularly wildlife, become persistently infected. Bovine tuberculosis (TB) is one such disease: its causative agent, Mycobacterium bovis , infects cattle, humans and multiple wildlife species including European badgers Meles meles . 2. In Britain, from 1974 to 1998 various strategies for the control of cattle TB involved culling badgers in the immediate vicinity of TB-affected herds. However, patterns of associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 23 publications
7
103
0
Order By: Relevance
“…Analyses of data on cubs are in the supporting information. We constructed a base model including three covariates considered likely to influence the probability of detecting infection (whether the carcass was stored Ͼ7 days, necropsy laboratory, and culture laboratory): one to represent geographical variation (trial area) and two previously found to influence prevalence (gender and tooth wear) (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of data on cubs are in the supporting information. We constructed a base model including three covariates considered likely to influence the probability of detecting infection (whether the carcass was stored Ͼ7 days, necropsy laboratory, and culture laboratory): one to represent geographical variation (trial area) and two previously found to influence prevalence (gender and tooth wear) (10).…”
Section: Methodsmentioning
confidence: 99%
“…However, even though patterns of M. bovis infection in cattle and badgers are associated in space (10), distinguishing badger-to-cattle transmission of infection, which has been demonstrated experimentally (3,4,11), from cattle-to-badger transmission is problematic in observational studies, especially where badgers are being sampled destructively. While the RBCT was in progress, measures to control a nationwide epidemic of foot-and-mouth disease (FMD) led to a 9-month suspension of routine cattle TB testing (12).…”
mentioning
confidence: 99%
“…generalized linear geostatistical models (GLGMs) [5, chapter 4] to analyse the data. To date, spatial association of infection in cattle has been mainly studied using nearest neighbour methods [6][7][8][9][10]. However, unlike GLGMs, these methods do not allow for spatial variation in population density, do not take covariates into account, or do not establish the range of clustering.…”
Section: Introductionmentioning
confidence: 99%
“…The social structure of animal populations significantly influences the transmission dynamics and persistence of infectious diseases (Altizer et al 2003;Perkins et al 2008;Woodroffe et al 2009). Knowledge of host interaction patterns is critical if we are to understand infectious disease transmission within a population (Cross et al 2005).…”
Section: Introductionmentioning
confidence: 99%